The efficiency of control in school self-economic management - Saleh Naji (PUBLISHINGS of Kostanay State Pedagogical Institute, 2016)
This article intends to study the efficiency of control in school self-economic management in elementary schools. A study was conducted on six schools, interviews were made with 6 principals. The results of the study indicated that the efficiency of control in school self-economic management was of high degree, which means that the principals should control the process of spending the budget on school requirements.
Keywords: concept of self-management of the school; efficiency; control in school self-management; opinion; perception